Physical education from the sidelines: pre-service teachers opportunities to teach in English primary schools. Issue 4 (19th May 2021) - Randall, Vicky; Griggs, Gerald
ABSTRACT: After two decades of political interest in primary Physical Education (PE) and school sport, the London 2012 Games (and its promised legacy) ushered in a new wave of government investment. To date, the impact of this funding on new entrants to the profession is unknown. This paper draws upon findings from the first phase of a national study that gives insights into the opportunities of pre-service primary teachers (PSTs) to teach PE. A short online survey was administered to PSTs across England. Data were collected to identify how many lessons of PE were taught and who delivered the subject in schools. Nearly 50% of PSTs reported they had no opportunity to teach PE, largely due to curriculum outsourcing. We caution, that if a persistent pattern of outsourcing remains, this could continue the removal of PSTs from teaching PE and the exclusion of teachers from the subject altogether.